2017
DOI: 10.5301/ejo.5001024
|View full text |Cite
|
Sign up to set email alerts
|

Long-term intraocular pressure after combined trabeculotomy-trabeculectomy in glaucoma associated with Sturge-Weber syndrome

Abstract: Combined trabeculotomy-trabeculectomy showed promising results as a treatment for SWS-associated glaucoma in children. Long-term visual and surgical outcomes are encouraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
(25 reference statements)
0
7
0
1
Order By: Relevance
“…Sood и соавт. выполнили указанное лечение на 24 глазах у 20 пациентов, успех был достигнут в 41,7% случаев в течение 134,7±67,7 месяцев [12].…”
Section: клинический случайunclassified
“…Sood и соавт. выполнили указанное лечение на 24 глазах у 20 пациентов, успех был достигнут в 41,7% случаев в течение 134,7±67,7 месяцев [12].…”
Section: клинический случайunclassified
“…[37][38][39]41] Combined trabeculotomy/trabeculectomy as the initial operation has been suggested in early onset glaucoma to address more distal resistance. [45][46][47][48] Recently, Sood et al [46] reported combined trabeculotomy/trabeculectomy in 24 eyes of 20 patients with SWS glaucoma with the overall success rate of 41.7% within 134.7 ± 67.7 months follow-up. Board and Shields investigated combined trabeculotomy/trabeculectomy in five SWS patients with the age ranging from 2 months to 15 years.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Earlier diagnosis of glaucoma and surgery at a median age of 3 months may afford a better success rate with a single trabeculotomy (Wu et al, ). Due to high risk of failure with single procedures, combined procedures, such as trabeculotomy‐trabeculectomy have been proposed as the first‐line approach in infants and children with ETA (Mandal, ; Mantelli et al, ; Sood, Rathore, Sood, Kumar, & Sood, ).…”
Section: Encephalotrigeminal Angiomatosis (Sturge‐weber Syndrome)mentioning
confidence: 99%
“…The type of angle surgery performed can be variable and goniotomy and trabeculotomy, which work by mechanically disrupting the anterior chamber angle structures, are often preferred as the initial surgical procedure for congenital glaucoma in children with ETA due to lower risk of adverse effects compared to filtering or tube surgery. Better IOP control can obtained by repeating the procedure, as initial goniotomy is only been proposed as the first-line approach in infants and children with ETA (Mandal, 1999;Mantelli et al, 2016;Sood, Rathore, Sood, Kumar, & Sood, 2018 (Friedman, 2002). Characteristic dermatologic features are caf e-au-lait spots and axillary freckling.…”
Section: Glaucoma Monitoring and Treatmentmentioning
confidence: 99%